2021
DOI: 10.1016/j.isci.2021.102091
|View full text |Cite
|
Sign up to set email alerts
|

Neural signaling modulates metabolism of gastric cancer

Abstract: Tumors comprise cancer cells and the associated stromal and immune/inflammatory cells, i.e., tumor microenvironment (TME). Here, we identify a metabolic signature of human and mouse model of gastric cancer and show that vagotomy in the mouse model reverses the metabolic reprogramming, reflected by metabolic switch from glutaminolysis to OXPHOS/glycolysis and normalization of the energy metabolism in cancer cells and TME. We next identify and validate SNAP25, mTOR, PDP1/a-KGDH, and glutaminolysis as drug target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 87 publications
(99 reference statements)
0
21
0
Order By: Relevance
“…However, limited evidence exists from preclinical studies showing an effect of devimistat on the TME or specific immune cell populations. One recent study from a gastroadenocarcinoma model highlighted improved survival in deinnervated gastric cancer treated with devimistat in combination with the mTOR inhibitor RAD001, highlighting a possible role for nervous tissue in the TME of these tumors ( 104 ). As a single agent, devimistat has been evaluated in multiple phase I studies, including in combination with modified FOLFIRINOX (mFOLFIRINOX) for pancreatic cancer ( 105 , 106 ) and in combination with cytarabine/mitoxantrone for relapsed/refractory AML.…”
Section: Metabolic Inhibitors In Clinical Trialsmentioning
confidence: 99%
“…However, limited evidence exists from preclinical studies showing an effect of devimistat on the TME or specific immune cell populations. One recent study from a gastroadenocarcinoma model highlighted improved survival in deinnervated gastric cancer treated with devimistat in combination with the mTOR inhibitor RAD001, highlighting a possible role for nervous tissue in the TME of these tumors ( 104 ). As a single agent, devimistat has been evaluated in multiple phase I studies, including in combination with modified FOLFIRINOX (mFOLFIRINOX) for pancreatic cancer ( 105 , 106 ) and in combination with cytarabine/mitoxantrone for relapsed/refractory AML.…”
Section: Metabolic Inhibitors In Clinical Trialsmentioning
confidence: 99%
“…In addition to its neurological aspects, SNAP25 research in oncology has received considerable attention in recent years. Recent studies have claimed that neural signalling is of great importance in regulating tumour metabolism and have validated the role of this biological function in regulating SNAP25 expression in gastric cancer metabolism [19]. Therefore, we performed a clinical relevance analysis of the SNAP25 gene in prostate cancer patients using the TCGA database.…”
Section: Discussionmentioning
confidence: 99%
“…SNAP25 has been seen as potentially important for normal vesicle fusion and lysosomal tra cking [17,18]. In recent years, a growing number of studies have identi ed an association between SNAP25 levels and gastric cancer [19], colon cancer [20], hepatocellular carcinoma [21], lung cancer [22] and papillary thyroid cancer [23]. However, the functions and mechanisms associated with SNAP25 activity in the immunologic and pathogenetic progression of prostate cancer remain to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have showed that denervation (surgically, pharmacologically or genetically) suppressed the tumorigenesis of gastric cancer, which was associated with a decrease in WNT/β-catenin signaling, the suppression of stem cell expansion through M3 receptor-mediated cholinergic signaling and the reversion of metabolic reprogramming, and that the combination of denervation and mono-chemotherapy led to an enhanced effect on tumor growth and survival in an animal model of gastric cancer (Zhao et al, 2014;Rabben et al, 2016). Recently, we have further shown that neural signaling modulated metabolism of gastric cancer, reflected by metabolic switch from glutaminolysis to OXPHOS/glycolysis and normalization of the energy metabolism after denervation (Rabben et al, 2021). In the present study, we wanted to explore the potential of a class of anti-cancer agents, isothiocyanates (ITCs) for chemoprevention and enhancement of chemotherapy as they are also shown to interfere with tumor metabolism (Conaway et al, 2002;Lv et al, 2020).…”
Section: Introductionmentioning
confidence: 94%